Current-Mode Shadow Filter with Single-Input Multiple-Output Using Current-Controlled Current Conveyors with Controlled Current Gain - Montree Kumngern; Fabian Khateb; Tomasz Kulej; Martin Kyselak; Somkiat Lerkvaranyu; Boonying Knobnob (My University, 2024)
In this paper, a novel current-mode shadow filter employing current-controlled current conveyors (CCCIIs) with controlled current gains is presented. The CCCII-based current-mode shadow filters are resistorless and can offer a number of advantages such as circuit simplicity and electronic tuning capability. The proposed shadow filters offer five filtering functions, i.e., low-pass, high-pass, band-pass, band-stop, and all-pass functions, in the same topology. Furthermore, no component matching condition is required to realize all the transfer functions. The natural frequency and quality factor adjustment is possible by using the CCCII current gains without the need to use external amplifiers, all capacitors are grounded, and the filter terminals offer low-input and high-output impedance. To verify the functionality and feasibility of the new topologies, the proposed circuits were simulated using SPICE and the transistor model process parameters NR100N (NPN) and PR100N (PNP) from AT&T’s bipolar arrays ALA400-CBIC-R. The simulation results are consistent with the theory. The CCCII experimental setup was designed using commercially available 2N3904 (NPN) and 2N3906 (PNP) transistors with a supply voltage of ±2.5 V. The measurement results confirm the performance of the designed filters.
Keywords: Spice; Current mirror; Analog and Mixed-Signal Circuit Design